Thru the years to '76 - Bicentennial West Fargo-Riverside History Book Committee; J&M Printing (North Dakota State Library, 1977)
A history of West Fargo, North Dakota including family biographies. 252 pages : illustrations, photographs 26 cm. Gordon is associated with the Salem Clinic. They have three daughters: Kirsten, Sonya and Marni. They live out of Salem where they have extensive property on which is a lake for fishing and swimming. They also have a stable for their riding horses. Audrey liked music and took piano lessons for several years. She accompanied musical groups in high school and also played in the band. After graduating from high school, she attended the Fairview School of Nursing in Minneapolis, Minnesota. Upon graduating in 1956, she worked at the Fairview Hospital. In 1957 she married Clarence Swenson, an accountant, of Minneapolis. They lived in Richfield, Minnesota until 1968 when they moved to Burnsville, Minnesota. They have four children: Cheryl, Scott, Douglas and Kathryn. The family enjoys Cross Country skiing and riding their horses. Both Gordon and Audrey and their families are active in their respective churches. SIG STEINOLFSON FAMILY Back row left to right: Arlson, Richard, Aileen. Front row left to right: Chris, Laura, Sam. Mr. and Mrs. Sig Steinolfson were born near Mountain, N. Dak., and except for three years during World War II, lived in that area until 1965, when they moved to West Fargo. Their present address is 502 - 2nd St. E., Tel. 282-3164. Sigurdur Steinolfson was born January 1, 1913. His parents were Mr. and Mrs. T. H. Steinolfson. Christbjorg Steinolfson was born April 23, 1917. Her parents were Mr. and Mrs. G. A. Christianson. Their parents were all of Icelandic descent. Mr. Christianson was born in Iceland and came to America with his parents when he was only two years old. Mrs. Christianson and Mr. and Mrs. Steinolfson were all born in America. Chris and Sam Steinolfson were married on July 6, 1940. During their first year of marriage Sam worked as a body mechanic at Byron's Garage, Mountain, for a salary of $45.00 per month. In 1942 they moved to Provo, S. Dak., where Sam worked for the Federal Government on construction of an ammunition depot. Five months later he went to work on bridge construction on the Alaskan Highway and Chris moved back to live with her parents. Sam later moved on to the Aleutian Islands where he worked on construction of barracks and also airplane hangars. He returned to Mountain on June 10, 1945. Chris spent most of this time living with her parents but spent part of 1944 with her sister, Mrs. Alden Strom, in Minneapolis, where their son, Richard, was born. In late 1944 she and Richard moved to a three-room home in Mountain. Since 1945 Mr. Steinolfson has worked on all types of construction. He is currently self-employed as a finishing carpenter. Mrs. Steinolfson has worked for Stanley Home Products for the last 12 years. Mr. and Mrs. Steinolfson were active members of the Vikur Lutheran Church, of Mountain, the oldest Icelandic church in North America. This church was built in 1884 and 1885 by the original settlers from Iceland. Sam was construction foreman when the church was remodeled, a basement built and the church moved. They both served on the church council, Sam being on the council many times both before and after they were married. Mrs. Steinolfson was a member of the Eyford Ladies Aid for many years. (Eyford is a rural community near Mountain). Their main objective was to help the needy in the community. She was a member of the Vikur Lutheran Church choir for over 20 years. Mr. and Mrs. Steinolfson are presently active members of the Faith Lutheran Church in West Fargo. Mr. and Mrs. Steinolfson have four children. Richard was born June 10, 1943. He graduated from High School in Mountain and from the University of North Dakota, Grand Forks, in 1965, with a Bachelor's degree in Mechanical Engineering. He received his Master's degree at the University of Colorado, Boulder, Colo. He also received his degree as Dr. of Philosophy in Aerospace Eng. Sciences there in June of 1971. He worked for Pratt & Whitney in West Palm Beach, Fla., for 2 years and then returned to Boulder, Colo., to work at the National Oceanic Atmospheric Administration Foundation where he was supported by a fellowship of the National Research 76 Scanned with a Zeutschel Zeta book scanner at 300 dpi. Edited with Multi-Page TIFF Editor.